Attenuation tomography of the western United States from ambient seismic noise (2011)
We show that the spatial coherency of the ambient seismic field can be used for attenuation tomography in the western United States. We evaluate the real portion of the spatial coherency with an elastic geometric spreading term (a Bessel function) and a distance dependent decay (an attenuation coefficient). In order to invert the spatial coherency, a weight stack inversion technique is applied. We recover phase velocity and attenuation coefficient maps at periods of 8–32s, which correspond to the elastic and anelastic structure at crustal and upper mantle depths. The phase velocity maps obtained by this method are of similar resolution to more standard two?station methods. The attenuation results provide an important complement to the information extracted from earthquake?based tomography. Several geological features are easily identifiable in the attenuation coefficient maps, such as the highly attenuating sedimentary basins along the West Coast of the United States, and the highly attenuating Yellowstone region, and the boundaries of the Snake River Plains.